PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogae L) PADA BERBAGAI JENIS DAN DOSIS BOKASHI PUPUK KANDANG - Andari, Ayu; Kadeko, Indrianto; Rahmi, Rahmi (Fakultas Pertanian, Universitas Tadulako, 2023)
This study was conducted at the Faculty of Agriculture Academic Gardens of Tadulako University between August and December 2021. The research used a two factorial randomized block design (RBD). The first factor was different types of manure bokashi, including no bokashi, chicken manure bokashi, cow manure bokashi, and goat manure bokashi. The second factor was the bokashi dose, comprising four levels: no bokashi, 10 t/ha, 15 t/ha, and 20 t/ha. Each treatment was replicated three times, resulting in a total of 48 experimental units. The findings revealed that there was no significant interaction between the bokashi dose and type of manure on the growth and yield of peanut plants. Among the various bokashi doses, the application of 20 t/ha resulted in the best growth and yields for peanuts. Additionally, when comparing different types of bokashi, the goat manure bokashi produced greatest peanut growth and yields.